Quaternary chalcogenides BaRE2In2Ch7 (RE = La–Nd; Ch = S, Se) containing InCh5 trigonal bipyramids. Issue 31 (18th July 2016) - Yin, Wenlong; Iyer, Abishek K.; Lin, Xinsong; Li, Chao; Yao, Jiyong; Mar, Arthur
Abstract : Infinite ribbons built from corner-sharing In-centred trigonal bipyramids, which are rare, are found in the structure of chalcogenides BaRE2 In2 Ch7 . Abstract : Eight new quaternary chalcogenides BaRE2 In2 Ch7 (RE = La–Nd; Ch = S, Se) have been prepared by reactions of BaCh, In2 Ch3, RE, and Ch at high temperatures. They adopt orthorhombic structures (space group Pbam, Z = 2; a = 11.6300(8)–11.5895(7) Å, b = 12.4202(9)–12.3001(8) Å, c = 4.0689(3)–4.0028(2) Å for the sulfides; a = 12.1515(6)–12.1358(10) Å, b = 12.9367(7)–12.8510(11) Å, c = 4.1966(2)–4.1363(4) Å for the selenides) containing one-dimensional anionic [In2 Ch7 ] ribbons of corner-sharing InCh5 trigonal bipyramids, separated by Ba and RE cations. The structure is an ordered variant of the rare Eu3 Sn2 S7 -type with Ba atoms occupying larger sites with nearly cubic geometry and RE atoms occupying smaller sites with bicapped trigonal prismatic geometry. The InCh5 trigonal bipyramids, which are unusual, exhibit four shorter In–Ch bonds and a fifth longer one. Band structure calculations indicate that BaLa2 In2 S7 is a direct gap semiconductor, and corroborate the description of the In coordination as CN4 + 1. On the basis of the optical absorption spectra, band gaps were estimated to be 1.87(2) eV for BaLa2 In2 S7 and 1.66(2) eV for BaLa2 In2 Se7 .